2019
DOI: 10.20448/journal.512.2019.61.71.78
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Chloride Dipping and Beeswax Coating on the Shelf Life and Quality of Nectarine (Prunus persica (L.) Batsch var. nucipersica) Fruits

Abstract: This research was conducted to evaluate the effect of CaCl2 dipping and beeswax (BW) coating on the shelf life and quality of nectarine fruits. The experiment was conducted under Holeta condition during the off-season of 2018. Fruits of '89-16N' nectarine variety were harvested from HARC orchard. The treatment consisted of a combination of four levels of CaCl2 (0%, 1.5%, 3.0% and 4.5%) and three levels of BW application (0%, 3% and 6%). The experiment was arranged in completely randomized design with factorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…These results were in accordance with the finding of Seleshi et al, (2019) in nectarine, who observed higher ascorbic acid content of nectarine fruits was maintained with CaCl 2 dipping and beeswax coating, particularly 3 % Bee Wax + 4.5 % CaCl 2 treated fruits.…”
Section: Ascorbic Acid(mg/100g Pulp)supporting
confidence: 92%
See 3 more Smart Citations
“…These results were in accordance with the finding of Seleshi et al, (2019) in nectarine, who observed higher ascorbic acid content of nectarine fruits was maintained with CaCl 2 dipping and beeswax coating, particularly 3 % Bee Wax + 4.5 % CaCl 2 treated fruits.…”
Section: Ascorbic Acid(mg/100g Pulp)supporting
confidence: 92%
“…Hence, the lowest PLW of the fruits could be effect of CaCl 2 dipping on respiration, which probably lowered the rate of transpiration, water loss and oxidation reactions and related to modified atmosphere created by wax coating. These results were in accordance with the finding of Seleshi et al, (2019) in nectarine, who observed treating nectarine fruits with 3 % BeesWax with 4.5 % CaCl 2 kept the PLW low up to the end of shelf life. The similar result on PLW was reported by Gaikwad et al, (2006) in mango and Dhumal et al, (2008) in aonla.…”
Section: Physiological Parameterssupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, beeswax is considered as important hydrophobic lipid based edible wax forming a protective layer against moisture losses and also imparts glossiness to the fruits [8]. Beeswax coatings were effective in maintaining various physico-chemical properties of fruits such as nectarines [9] and plums [10]. Elementary information is available on effect of beeswax [11] and AVG [12] on physico-chemical characteristics of mango fruits under low temperature storage conditions.…”
Section: Introductionmentioning
confidence: 99%